Double Vision After Minimally Invasive Orbital Decompression. Issue 5 (July 2017) - Golan, Shani; Gupta, Adit; Goldberg, Robert A.
Abstract : Introduction: New onset Diplopia following orbital decompression in thyroid eye disease patients is estimated to occur in up to 30% to 40% of decompression patients, mostly related to deep lateral and medial wall decompressions. Methods: A retrospective chart review of all minimally invasive (fat and minimal bone orbital decompression performed at the UCLA Stein Eye Institute between 2005 and 2015. Inclusion criteria were thyroid eye disease patients older than 18 years undergoing fat only orbital decompression with no previous muscle surgery. Results: The chart review revealed only 5 patients with new onset diplopia after this surgery. The cases are discussed and a possible mechanism for the diplopia is proposed. Discussion: Double vision following minimally invasive orbital decompression is rare and the mechanisms are poorly understood.